Asuhan Keperawatan Maternitas Pada Pasien Dengan Post Op Sectio Caesarea Di Ruang Kebidanan RSUD Prof M Yamin Pariaman - zalia qotiva; Reska Handayani; Prima Yoselina; Yessy Aprihatin (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Cephalopelvic Disproportion (CPD) is a condition of mismatch between the dimensions of the fetal head and the capacity of the mother's pelvis. Sectio cesarea is a surgical delivery process, where surgery is performed by making an incision in the abdomen and uterus. WHO sets the SC rate at 5–15%, while in Indonesia it reaches 17.6%, West Sumatra Province recorded 121 cases of maternal death, 55 cases (45.5%) with a Cephalopelvic Disproportion (CPD) rate (4.6%), while at the research site, namely at Prof. H. M Yamin, SH, Pariaman Regional Hospital where CPD ranks 4 of the 10 most common diseases in the obstetrics room. This study aims to apply nursing care to Cephalopelvic Disproportion (CPD) patients through the stages of assessment, diagnosis, intervention, implementation and evaluation of nursing. The writing is done in the form of a case study on one patient managed in the obstetrics room of Prof. H. M Yamin, SH, Pariaman. H. M Yamin, SH, Pariaman City, on February 1 to 5, 2026. The results of the study obtained four nursing problems, namely: acute pain, impaired physical mobility, risk of infection, and ineffective breastfeeding. Interventions carried out included pain management, mobilization support, infection prevention, and lactation counseling. The evaluation results obtained 3 nursing problems resolved, while the problem of ineffective breastfeeding nursing had not been resolved until the 5th day of nursing care. It is hoped that the results of this writing can be a reference for health workers in improving the skills of providing nursing care to patients with post-op sectio cesarean. In addition, patients and families are also expected to increase their knowledge and implement a healthy lifestyle in a sustainable manner.